Mean markets and lizard brains : - Burnham, Terry (John Wiley & Sons, Inc, 2005)
Mean Markets and Lizard Brains converts cutting-edge intellectual developments into practical investment steps. Filled with in-depth insights and real-world advice, this guide: Provides a timeless blueprint for effective and low-stress investing through a thorough examination and explanation of the lizard brain; Summarizes the key findings of the science of irrationality and reveals the biological forces that cause even the smartest of people to make systematic mistakes; Sets the macroeconomic stage for choosing investments, with discussions of the economy, inflation, and the value of the U.S. dollar.; Evaluates investments based on understanding how the lizard brain operates in today's global macroeconomic landscape